Grounds for dialogue: Intersectionality and superdiversity - Khazaei, Faten (My University, 2018)
This paper investigates the possibility of a fruitful dialogue between intersectionality and superdiversity. It argues that, despite the shortcomings of superdiversity, the complex migration-related configurations it focuses on can enable intersectionality to overcome some of its own challenges by becoming more precise and accurate. To empirically expose the mechanisms through which race-, gender-, and class-based inequalities are reproduced, it is necessary to anchor those mechanisms in a specific time and space ‐ a historical, social, economic, and legal context. Through a case study of institutional responses to domestic violence, the paper demonstrates that superdiversity can help clarify the context in which these responses occur. Finally, by distinguishing between the object of study (the intersectional construction of disadvantage and prejudice) and the object of observation (public institutions where superdiverse situations are created by migration-related configurations), this paper examines a challenging situation for intersectional analysis in the context of Switzerland, a context that opens up to surprising articulations of discrimination and inequality for ‘migrants’ subjects to domestic violence.
Keywords: domestic violence; empirical operationalisation; intersectionality; migration-related diversity; superdiversity